2012
DOI: 10.1371/journal.pone.0052332
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Promotes Collagen Accumulation in Crohn’s Disease Fibrosis by Down-Regulation of Fibroblast MMP Synthesis: A Role for Innate Lymphoid Cells?

Abstract: BackgroundFibrosis is a serious consequence of Crohn’s disease (CD), often necessitating surgical resection. We examined the hypothesis that IL-13 may promote collagen accumulation within the CD muscle microenvironment.MethodsFactors potentially modulating collagen deposition were examined in intestinal tissue samples from fibrotic (f) CD and compared with cancer control (C), ulcerative colitis (UC) and uninvolved (u) CD. Mechanisms attributable to IL-13 were analysed using cell lines derived from uninvolved m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 39 publications
2
91
2
Order By: Relevance
“…Conversely, IL-1β and collagen levels in the supernatants and TGF-β1 transcripts in the homogenates of cultured explants were markedly higher in strictured CD. Our data are in contrast with the observation by Bailey et al [24] that IL-13 mRNA is overexpressed in the lysates of fibrotic intestinal muscle of CD patients compared with that in control subjects, however this discrepancy may be explained by post-transcriptional modifications which may ultimately determine IL-13 protein level.Given the lack of information on the gut mucosal distribution of IL-13Rs, we investigated their expression by different LPMC subtypes in inflammatory bowel disease and control mucosa. In particular, since IL-13 can bind to IL-13Rα2 or to the heterodimer formed by IL-13Rα1 and IL-4Rα [26], we assessed by flow cytometry the expression of IL-4Rα, IL-13Rα1 and IL-13Rα2 on the surface and in the cytoplasm of T cells (CD3 + cells) and macrophages (CD68 + cells) from healthy mucosa of control subjects, from inflamed UC and CD mucosa, and from the mucosa overlying CD strictures and CD mucosa above non-strictured areas.…”
contrasting
confidence: 99%
“…Conversely, IL-1β and collagen levels in the supernatants and TGF-β1 transcripts in the homogenates of cultured explants were markedly higher in strictured CD. Our data are in contrast with the observation by Bailey et al [24] that IL-13 mRNA is overexpressed in the lysates of fibrotic intestinal muscle of CD patients compared with that in control subjects, however this discrepancy may be explained by post-transcriptional modifications which may ultimately determine IL-13 protein level.Given the lack of information on the gut mucosal distribution of IL-13Rs, we investigated their expression by different LPMC subtypes in inflammatory bowel disease and control mucosa. In particular, since IL-13 can bind to IL-13Rα2 or to the heterodimer formed by IL-13Rα1 and IL-4Rα [26], we assessed by flow cytometry the expression of IL-4Rα, IL-13Rα1 and IL-13Rα2 on the surface and in the cytoplasm of T cells (CD3 + cells) and macrophages (CD68 + cells) from healthy mucosa of control subjects, from inflamed UC and CD mucosa, and from the mucosa overlying CD strictures and CD mucosa above non-strictured areas.…”
contrasting
confidence: 99%
“…Conversely, other studies have suggested that ILC2s and eosinophils are contributing factors to CD progression through an IL-13 dependent accumulation of matrix-producing fibroblasts (16,17). Thus, there is evidence to support both Th2 and Th17 responses in the pathology of CD.…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, increased levels of IL-13 in the fibrotic intestine of CD patients are produced by a previously not described population of cells expressing high levels of IL-13Ra 1 and IL-13 in the muscle layer of CD intestine. 39 The phenotype of these cells (KIR…”
Section: Molecules Of Potential Pathophysiological Relevance During Fmentioning
confidence: 99%